The TATA box promoter region of maize Adh1 affects its organ-specific expression. - Kloeckener-Gruissem, B (1992)
We have isolated two lineage-related Mutator (Mu3) transposon-induced Adh1 promoter mutants in maize: Adh1-3F1124 carries a duplicated TATA box and its revertant, Adh1-3F1124r17, bears a deleted TATA box. Both alterations lead to unique patterns of organ-specific ADH1 enzyme expression. Enzyme activity in Adh1-3F1124 sporophytic organs (scutellum and roots) is greatly reduced, while activity levels remain normal in the male gametophyte (pollen). Conversely, enzyme activity in Adh1-3F1124r17 roots and scutellum is partially restored, but is concomitantly reduced in pollen. Transcript analysis suggests (i) that the TATA box region of the Adh1 gene influences post-transcriptional processes in the male gametophyte but not in roots and (ii) that organ-specific transcription signals in the promoter are distinct from the previously identified anaerobic environment-specific cis-acting transcription signals. Different organs appear to provide surrogate TATA function in different ways, leading to organ-specific differences in the length of the Adh1 message 5' leader.